Pengaruh Lama Penyimpanan Ekstrak Kasar Daun Mahkota Dewa (Phaleria macrocarpa) terhadap Mortalitas Keong Mas (Pomacea canaliculata) - Rusdi Rusli; Winarto Winarto; Jogi Aprihan Putra (Jurnal Proteksi Tanaman, 2020)
Mahkota dewa [Phaleria macrocarpa (Scheff) Boerl] contains saponin that can be used as a botanical pesticide, including molluscicide. This study aimed to obtain the most effective storage time of leaf crude extract of mahkota dewa on the mortality of golden snail. The application was carried out in the greenhouse of Faculty of Agriculture of Universitas Andalas from March to May 2019. The study used a Randomized Block Design (RBD) consisting of time of storage, i.e., 0 day (2 hours), two days, four days, six days, and eight days those were applied to early-stage, late-stage, male and female of golden snail. The results showed that all storage time of mahkota dewa leaf crude extract had the same effect on early state golden snail mortality. However, at late state golden snail 0 day and two days, storage times were the best. Two days of storage time caused mortality of early-stage, late-stage, and male adult of the golden snail, however, 0 days (2 hours) for female adult. Keywords: Mahkota dewa, golden snail, storage time